Evaluation of Bedtime vs. Morning Levothyroxine Intake to Control Hypothyroidism in Older Patients: A Pragmatic Crossover Randomized Clinical Trial - de Mello, Renato Bandeira; Giassi, Karina; Stahl, Gabriela; Machado Assis, Maria Luisa; Flores, Marina Siqueira; de Lima, Bruna Cambrussi; Piccoli, Vanessa; da Costa Rodrigues, Ticiana (Frontiers in Medicine, 2022)
Introduction: Drug scheduling in older adults can be a challenge, especially considering polypharmacy, physical dependency, and possible drug interactions. Properly testing alternative treatment regimens could therefore help overcome treatment barriers. Hypothyroidism is a common disease related to aging and its treatment demands a rigorous drug schedule to avoid drug-drug and drug-food interactions. Most studies testing an evening administration of Levothyroxine were mainly composed of younger adults. Therefore, this trial aims to assess if evening levothyroxine (LT4) administration can effectively control hypothyroidism in older patients. Materials and Methods: A randomized crossover clinical trial was conducted between June/2018 and March/2020 at the Hospital de Clínicas de Porto Alegre, a teaching hospital in Brazil, to compare the efficacy of morning and evening administration of LT4 for hypothyroidism control in older patients. The study protocol is published elsewhere. A total of 201 participants, ≥60 years old, with primary hypothyroidism treated with LT4 for at least 6 months, and on stable doses for at least 3 months were included. Participants were randomly assigned to a starting group of morning LT4 intake (60 minutes before breakfast) or bedtime LT4 intake (60 minutes after the last meal). After ≥12 weeks of follow-up, crossover between strategies was performed. The primary outcome was the change in serum thyrotropin (TSH) levels after 12 weeks of each LT4 administration regimen. Results: A total of 201 participants of mean age 72.4±7.2 years were included, out of which 84.1% were women; baseline characteristics and frequency of controlled hypothyroidism were similar between groups. Mean baseline TSH was 3.43±0.25 mUI/L. 118 participants attended three meetings, allowing 135 comparisons by crossover analytic strategy. Mean TSH levels after follow-up were 2.95±2.86 in the morning group and 3.64±2.86 in the bedtime group, p=0.107. Discussion: TSH levels and frequency of controlled hypothyroidism were similar during the follow-up period regardless of the treatment regimen (morning or bedtime).